Analysis Of Differences In Onion Drying Systems With Steam Fan Collectors And Ovens - Ayub Januari Sidauruk; Win Fronstein Naibaho; Tambos August Sianturi; Jhon Sufriadi Purba; Shalom Hilton Siahaan (International journal of technology and education research, 2026)
This study aims to analyze the differences System Drying Shallots With Collector Fan Steam and Oven. Based on results study drying onion red using a drying oven with method displacement hot convection and radiation, then can concluded as following Process drying cause occurrence decline heavy material in a way gradually from 9 kg to 4.4 kg. Weight loss heavy happen Because water content in material evaporate during the heating process. Transfer hot convection happen consequence flow air heat directly in the oven about surface material. The size displacement hot convection increase along increase oven temperature. Transfer hot radiation happen through radiance hot from element oven heater towards materials. Radiant heat help speed up the evaporation process water content in onions red. Calculation results show that the more tall temperature drying, then displacement the heat that occurs the more big so that the drying process ongoing more fast. Use of drying oven proven effective in lower moisture content of the material and speed up the drying process onion red